Nasal delivery of killed Bacillus subtilis spores protects against influenza, RSV and SARS-CoV-2 - Xu, Rong; Hong, Huynh A.; Khandaker, Shadia; Baltazar, Murielle; Allehyani, Noor; Beentjes, Daan; Prince, Tessa; Ho, Yen-Linh; Nguyen, Linh Hanh; Hynes, Daniel; Love, William; Cutting, Simon M.; et al. (Frontiers in Immunology, 2025)
IntroductionSpores of the bacterium Bacillus subtilis (B. subtilis) have been shown to carry a number of properties potentially beneficial for vaccination. Firstly, as vehicles enabling mucosal delivery of heterologous antigens and secondly, as stimulators of innate immunity. Here, we have examined the specificity of protection conferred by the spore-induced innate response, focusing on influenza H1N1, respiratory syncytial virus (RSV), and coronavirus-2 (SARS-CoV-2) infections.MethodsIn vivo viral challenge murine models were used to assess the prophylactic anti-viral effects of B. subtilis spores delivered by intranasal instilling, using an optimised three-dose regimen. Multiple nasal boosting doses following intramuscular priming with SARS-CoV-2 spike protein was also tested for the capability of spores on enhancing the efficacy of parenteral vaccination. To determine the impact of spores on immune cell trafficking to lungs, we used intravascular staining to characterise cellular participants in spore-dosed pulmonary compartments (airway and lung parenchyma) before and after viral challenge.ResultsWe found that mice pre-treated with spores developed resistance to all three pathogens and, in each case, exhibited a significant improvement in both survival rate and disease severity. Intranasal spore dosing expanded alveolar macrophages and induced recruitment of leukocyte populations, providing a cellular mechanism for the protection. Most importantly, virus-induced inflammatory leukocyte infiltration was attenuated in spore-treated lungs, which may alleviate the associated collateral tissue damage that leads to the development of severe conditions. Remarkably, spores were able to promote the induction of tissue-resident memory T cells, and, when administered following an intramuscular prime with SARS-CoV-2 spike protein, increased the levels of anti-spike IgA and IgG in the lung and serum.ConclusionsTaken together, our results show that Bacillus spores are able to regulate both innate and adaptive immunity, providing heterologous protection against a variety of important respiratory viruses of high global disease burden.